2019
DOI: 10.1155/2019/2628747
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Antioxidant Activity of Sweet Basil (Ocimum basilicum L.) Essential Oil on Ground Beef from Boran and Nguni Cattle

Abstract: The global meat industry is characterised by a growing interest in natural preservative additives. This study determined the effect of sweet basil (Ocimum basilicum L.) essential oil (SBEO) on colour and lipid oxidation in minced beef. The phytoconstituents of SBEO were analyzed by gas chromatography mass spectrometry. Thereafter, minced beef samples from Nguni and Boran cattle were treated with either no additives (control, C) or SBEO added at 2% (SB2), 4% (SB4), or 6% (SB6). The meat samples were aerobically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 33 publications
5
37
0
1
Order By: Relevance
“…The coating without EOs (CC) provided an oxygen transfer barrier resulting in samples showing lower TBARS than the control. The antioxidant effect showed by the AC samples is in agreement with a report using 4%-6% BEO that did not find TBARS in raw minced meat packed in polyethylene bags at 4 • C [17]. In addition, BEO contains eugenol (Table 1) that is able to donate electrons to inactivate free radicals involved in the propagation step of autoxidation, besides its protective effect against prooxidants like iron [15,16,18].…”
Section: Physicochemical Propertiessupporting
confidence: 90%
“…The coating without EOs (CC) provided an oxygen transfer barrier resulting in samples showing lower TBARS than the control. The antioxidant effect showed by the AC samples is in agreement with a report using 4%-6% BEO that did not find TBARS in raw minced meat packed in polyethylene bags at 4 • C [17]. In addition, BEO contains eugenol (Table 1) that is able to donate electrons to inactivate free radicals involved in the propagation step of autoxidation, besides its protective effect against prooxidants like iron [15,16,18].…”
Section: Physicochemical Propertiessupporting
confidence: 90%
“…There are studies performed in the past, up until recent years, investigating the antioxidant characteristics of Nigella sativa L. (black cumin) [ 181 , 188 , 189 , 190 , 191 ], and in all these reports, the antioxidant activity of Nigella sativa L. (black cumin) EO has been mentioned. Ocimum basilicum L. (basil) is another plant EO that has been used in recent antioxidant studies [ 182 , 192 , 193 ]. Ahmed et al [ 182 ] observed that although the EOs of Ocimum basilicum L. (basil) collected from several regions have the same three major components—linalool, estragole, and methyl cinnamate—the difference in their percentages were interpreted as a reason for the significant differences in their antioxidant activities.…”
Section: Antioxidant Activities Of Essential Oilsmentioning
confidence: 99%
“…Different test methods have been applied, and it becomes to be understood between the complete essential oil and individual components [70][71][72][73]. A strong chelating effect on metals as iron or copper has been reported to diminish the presence of ROS obtained from reactions bar with these metals [74].…”
Section: Oxidant Activitymentioning
confidence: 99%